Simultaneous localization and mapping and the situativeness of a new generation of geomedia technologies. Issue 2 (June 2019) - Kanderske, Max; Thielmann, Tristan
Simultaneous localization and mapping technology is commonly used within mobile devices and household appliances—it allows our vacuum robot to navigate the living room and enables us to view augmented reality content on our smartphones. By examining simultaneous localization and mapping–based devices and contrasting them against more traditional forms of cartographic practices, we argue that simultaneous localization and mapping technology not only opens up interior spaces for geographic examination but also calls into question the categorical difference between inside and outside itself. As with simultaneous localization and mapping, the mathematical construction of the surrounding space happens in the moment of its detection, simultaneous localization and mapping exhibits a moment of radical situativeness that is freed from the constraints of a stabilized, external database. We propose that this moment of situativeness, which is also inscribed into the resulting highly mobile and fluid visualizations, is the defining feature of a new kind of geomedia that simultaneously establish a vertical and a horizontal geography.